Genetic characterization of porcine circovirus type 2 (PCV2) from wild boars detected in different regions of Ukraine - Dudar, L.V.; Budzanivska, I.G.; Polishchuk, V.P. (Вiopolymers and Cell, 2018)
Circovirus type 2 are an extremely common swine virus in terms of [is a swine virus extremely widespread in] industrial farming worldwide, including Ukraine]. A similar situation was de-scribed in Ukraine. It leads to an immunosuppressive condition of animals and high mortality of animals. Due to the [Considering a] variety of PCV-2 strains in the world, and the difference be-tween strains common in wildlife and farms, [it is necessary to characterize] the characterization of field isolates found among wild boars in Ukraine is required. So, in this work [the] isolates from wild boars from different regions of Ukraine were characterized and differentiated by phy-logenent [phylogenetic] analysis. As a result of the study, it was shown that [the] isolates from the Chernihiv, Zaporizhzhya, Cherkasy and Kharkiv regions belong to different subgroups of the PCV-2 and have different origin. In addition [Additionally], a relatively high level of similarity with the isolates from Croatia and Brazil has been established. At the same time, the similarity of isolates isolated from wild boars from the Zaporizhzhya and Chernihiv oblasts has been shown to have been isolated from pigs from industrial farms. [At the same time, it has been shown the simi-larity of isolates from wild boars from the Zaporizhzhya and Chernihiv regions with those from pigs of industrial farms.] Цирковірус свиней 2 типу є надзвичайно розповсюдженим у всьому світі вірусом серед свиней в умовах промислового вирощування. Ураження вірусом призводить до імуносупресивного стану тварин та високої смертності. З огляду на велику різноманітність штамів ЦВС-2 у світі, та відмінність між штамами, розповсюдженими в дикій природі та на фермах, необхідною є характеристика польових ізолятів, виявлених в Україні серед диких кабанів. Мета. Охарактеризувати та диференціювати ізоляти ЦВС-2, виділені від диких кабанів з різних регіонів України. Методи. Філогенентичний аналіз. Результати. Показано, що ізоляти з Чернігівської, Запорізької, Черкаської та Харківської областей належать до різних субгруп ЦВС-2 та мають різне походження. Крім того, встановлено досить високий рівень їхньої подібності з ізолятами з Хорватії та Бразилії. Водночас, показано подібність ізолятів, виділених від диких кабанів із Запорізької та Чернігівської областей з такими, що були виділені від свиней з промислових господарств. Висновки. Цирковирус свиней 2 типа является чрезвычайно распространенным во всем мире вирусом среди свиней в условиях промышленного выращивания. Заражение вируса приводит к иммуносупрессивному состоянию животных и высокой смертности. Учитывая большое разнообразие штаммов ЦВС-2 в мире, и различие между штаммами, распространенными в дикой природе и на фермах, необходима характеристика полевых изолятов, выявленных в Украине среди диких кабанов. Цель. Охарактеризовать и дифференцировать изоляты ЦВС-2, выделенные от диких кабанов из разных регионов Украины. Методы. Филогенентический анализ . Результаты. Показано, что изоляты из Черниговской, Запорожской, Черкасской и Харьковской областей относятся к различным субгрупам ЦВС-2 и имеют разное происхождение. Кроме того, установлено достаточно высокий уровень их сходства с изолятами из Хорватии и Бразилии. В то же время, показано сходство изолятов, выделенных от диких кабанов Запорожской и Черниговской областей, с выделенными от свиней из промышленных хозяйств. Выводы. Ключевые слова: цирковирус свиней 2 типа, дикие кабаны, филогенетический анализ, генетическое разнообразие.